CHARACTER DISCOURSE BETWEEN STUDENTS AND SCHOOL TEACHERS IN YOGYAKARTA SPECIAL PROVINCE IN INDONESIA - Slamet Suyanto (Jurnal Pendidikan Karakter, 2016)
Abstract: One of the critical points in character education in schools is the perception of good and bad characters between students and teachers. If there is a discourse on the perception, then there will be misleading on the character building in the classroom. The students who perceive that they do have good attitudes and perform good characters might be judged by the teacher as bad students. On the contrary, the teachers who believe that they have good attitudes and perform good characters might be considered by the students as disliked teachers. This survey research was conducted in 6 middle schools in Yogyakarta Special Province, involving 120 students and 120 teachers. The instrument of the research was mainly questionnaires consisting of three main groups of characters, namely performance, attitude, and behavior. Data were analyzed descriptively using a percentage. Inter-rater agreement analysis was administered to know the character admiration and discourse. The results indicate that there are some discourses between the students and the teachers on the behaviors, performance, and attitudes. Keywords: character education, character discourse, character admiration WACANA KARAKTER ANTARA SISWA DAN GURU SEKOLAH DI DAERAH ISTIMEWA YOGYAKARTA INDONESIA Abstrak: Salah satu poin penting dalam pendidikan karakter di sekolah adalah persepsi karakter baik dan buruk antara siswa dan guru. Jika ada wacana tentang persepsi, maka akan ada menyesatkan pada pembangunan karakter di dalam kelas. Para siswa yang merasa bahwa mereka memiliki sikap yang baik dan melakukan karakter yang baik mungkin akan dinilai oleh guru sebagai siswa yang buruk. Sebaliknya, para guru yang percaya bahwa mereka memiliki sikap yang baik dan melakukan karakter yang baik mungkin dianggap sebagai siswa yang tidak baik oleh guru. Penelitian survei ini dilakukan di 6 sekolah menengah di Provinsi Daerah Istimewa Yogyakarta yang melibatkan 120 siswa dan 120 guru. Instrumen penelitian ini terutama kuesioner yang terdiri atas tiga kelompok utama karakter, yaitu kinerja, sikap, dan perilaku. Data dianalisis secara deskriptif dengan menggunakan persentase. Analisis perjanjian antarpenilai diberikan untuk mengetahui kekaguman karakter dan wacana. Hasil penelitian menunjukkan bahwa ada beberapa wacana antara siswa dan guru pada perilaku, kinerja, dan sikap. Kata Kunci: pendidikan karakter, wacana karakter, kekaguman karakter